Advancements in Nano-Delivery Systems for Photodynamic and Photothermal Therapy to Induce Immunogenic Cell Death in Tumor Immunotherapy - Zhao R; Li S; Zhao J; Yao C (International Journal of Nanomedicine, 2025)
Rui Zhao,1,2,* Shuai Li,1,* Jingyuan Zhao,3 Chenhui Yao4 1Department of Pharmacy, The First Affiliated Hospital of Dalian Medical University, Dalian, People’s Republic of China; 2College of Pharmacy, Dalian Medical University, Dalian, People’s Republic of China; 3Clinical Laboratory Center, Central Hospital of Dalian University of Technology, Dalian, People’s Republic of China; 4Department of General Surgery, The First Affiliated Hospital of Dalian Medical University, Dalian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chenhui Yao, Department of general surgery, The First Affiliated Hospital of Dalian Medical University, Dalian, People’s Republic of China, Email gavinyaoch@126.com Jingyuan Zhao, Clinical Laboratory Center, Central Hospital of Dalian University of Technology, Dalian, People’s Republic of China, Email zhaojingyuanlab@outlook.comAbstract: Inducing immunogenic cell death (ICD) can tackle the issue of low immune response levels in tumor immunotherapy. Photodynamic therapy (PDT) uses photosensitizers to generate reactive oxygen species that kill tumor cells, while photothermal therapy (PTT) directly uses heat from photothermal converters to destroy tumor cells. However, these single treatments have their limitations. The development of optical therapy nanodelivery systems, along with the combination of PTT/PDT with chemotherapy and immunotherapy, offers new strategies for tumor immunotherapy. This article explores the application of PDT and PTT mediated by nanodelivery systems in promoting immunogenic cell death in tumor cells. This article explores nano-delivery systems that precisely release photosensitizers to boost efficacy and reduce toxicity. It also discusses their potential for combination therapy through co-delivery, utilizing multimodal strategies to enhance both phototherapy and chemotherapy, thus improving anticancer effectiveness.Keywords: photodynamic therapy, photothermal therapy, immunogenic cell death, delivery system, nano